The Relation Between Perceived Stigma And Social Support Among Substance Abusers In Pusat Pemulihan Penagihan Narkotik (Puspen), Karangan, Kedah - Pradeep Raj A/L Nadaraja (Universiti Sains Islam Malaysia, 2024)
Matric: 3211011 (FKP)-Restricted until Aug 2025